Effects of training in an aero position on metabolic economy - Peveler, W.; Bishop, P.; Smith, J.; Richardson, M. (Journal of Exercise Physiology online, 2005)
Previous studies have examined the metabolic cost of cycling in an aerodynamic position and found that there was a greater metabolic cost in this position when compared to an upright position. These studies only examined cyclists who train upright. This study compared cyclist who only train in an upright position and triathletes who only train in an aero position to determine if there was specificity to training position. Both groups completed two 30-min trials (one trial upright and the other aero) on two different days at the Watts at 70% of VO2max and VO2 was recorded. It was found that the mean VO2 of the aero position (43.3 ± 5.5 mL/kg/min) was significantly higher than the upright position (41.2 ± 5.8 mL/kg/min) for cyclist and the means between aero (38.5 mL/kg/min ± 5.4) and upright positions (38.0 ± 5.3 mL/kg/min) were not significantly different for triathletes at p<0.05. There does not appear to be the normal metabolic cost associated with riding in an aero position when examining triathletes who train only in that position. From this study it can be recommended that cyclists and triathletes should train in the position in which they race.